Optimization of Makodam Jaya (Telegram Bot Application Management) Increases Satisfaction with Registration Services at Posyandu Klopo Sepuluh - M. Suhron; Rustandi; Novi Anggraeni (Universitas STRADA Indonesia, 2025)
Background: The waiting time for registration services at Posyandu is the community's first service, the waiting time for health service registration at Posyandu according to Posyandu standards is 3-5 minutes, but this has experienced delays or increased waiting times. Purpose: Analyzing the satisfaction of registration services with the Makodam Jaya (Telegram Bot Application Management) at Posyandu Klopo Sepuluh. Methods: Type of experimental research: pre-post test One Group Design, sampling technique with purposive sampling, sample size of 113 mothers analyzed statistically using the Wilcoxon test. Results: There are differences in the Tangible, Reliability, Responsiveness, Assurance and Empathy indicators of satisfaction of registration services between before and after the intervention was given, apart from that, based on the Wilcoxon Test analysis on satisfaction, the P value was (0.000) < α (0.05). Conclusion: Makodam Jaya Innovation (Telegram Bot Application Management) Increases Satisfaction with Registration Services including Tangible, reliable, Responsiveness, Assurance, and Empathy indicators at Posyandu Klopo Sepuluh.